Morphology and Metaphilosophy: Goethe, Wittgenstein and Waismann - Coliva, Annalisa (Nordic Wittgenstein Review, 2024)
The paper explores how Wittgenstein and Waismann interpreted Goethe’s ideas from The Metamorphosis of Plants. These ideas laid the foundation for Wittgenstein’s concept of “family resemblance”, which Waismann also embraced in The Principles of Linguistic Philosophy. However, the paper argues that Wittgenstein’s and Waismann’s metaphilosophical implications evolved differently in their later works. Notably, it is Waismann, rather than Wittgenstein, who took these ideas to their extreme, concluding in How I See Philosophy that all forms of philosophical theorizing should be rejected. By contrast, Wittgenstein rejected only the kind of theorizing in philosophy which aims at offering monistic and reductionist explanations of key philosophical concepts.